Approaches for enhancing patient-reported experience measurement with ethnically diverse communities: a rapid evidence synthesis - Reema Harrison; Maha Pervaz Iqbal; Upma Chitkara; Corey Adams; Ashfaq Chauhan; Rebecca Mitchell; Elizabeth Manias; Megan Alston; Anne Marie Hadley (BMC, 2024)
Abstract Background Patient-reported experience measures (PREMs) are used to drive and evaluate unit and organisational-level healthcare improvement, but also at a population level, these measures can be key indicators of healthcare quality. Current evidence indicates that ethnically diverse communities frequently experience poorer care quality and outcomes, with PREMs data required from this population to direct service improvement efforts. This review synthesises evidence of the methods and approaches used to promote participation in PREMs among ethnically diverse populations. Methods A rapid evidence appraisal (REA) methodology was utilised to identify the disparate literature on this topic. A search strategy was developed and applied to three major electronic databases in July 2022 (Medline; PsycINFO and CINAHL), in addition to websites of health agencies in Organisation for Economic Co-operation and Development countries via grey literature searches. A narrative evidence synthesis was undertaken to address the review question. Results The review resulted in 97 included studies, comprised 86 articles from electronic database searches and 11 articles from the grey literature. Data extraction and synthesis identified five strategies used in PREM instruments and processes to enhance participation among ethnically diverse communities. Strategies applied sought to better inform communities about PREMs, to create accessible PREMs instruments, to support PREMs completion and to include culturally relevant topics. Several methods were used, predominantly drawing upon bicultural workers, translation, and community outreach to access and support communities at one or more stages of design or administration of PREMs. Limited evidence was available of the effectiveness of the identified methods and strategies. PREMs topics of trust, cultural responsiveness, care navigation and coordination were identified as pertinent to and frequently explored with this population. Conclusions The findings provide a basis for a maturity model that may guide change to increase participation of ethnically diverse communities in PREMs. In the short-medium term, health systems and services must be able to recognise and respond to cultural and linguistic diversity in the population when applying existing PREMs. In the longer-term, by working in collaboration with ethnically diverse communities, systems and services may co-create adapted or novel PREMs that tackle the factors that currently inhibit uptake and completion among ethnically diverse communities.